Fundamentals of Business Law - Randall, Melissa; Students, Community College of Denver (Open textbook library., 2020)
Undergraduate business law textbook written by Melissa Randall and Community College of Denver Students in collaboration with lawyers and business professionals for use in required 200 level business law courses in the United States. This book is an introductory survey of the legal topics required in undergraduate business law classes.